Verified software: theories, tools, and experiments : 7th International Conference, VSTTE 2015, San Francisco, CA, USA, July 18-19, 2015 : revised selected papers /: 7th International Conference, VSTTE 2015, San Francisco, CA, USA, July 18-19, 2015 : revised selected papers. (2016) - Unknown
No abstract available